The influence of cross-sectional morphology on the compressive resistance of polymeric nerve conduits. (18th July 2018) - Yin, Jun; Zhang, Deming; Xiang, Yang; Wei, Peng; Yang, Zhenyu; Wang, Zonghuan; Fu, Jianzhong
Abstract: Artificial nerve conduits are proposed as an alternative to repair peripheral nerves injuries; while mechanical properties are of great importance for successful clinical application of nerve conduits. In this work, the poly (d, l -lactide- co -glycolide) (PLGA) nerve conduits were fabricated by the dry-jet wet spinning, and the compressive resistance of nerve conduits was systematically measured. It was found that the compressive resistance of nerve conduits significantly increased with the PLGA concentration of dope fluids. A numerical model was developed to simulate the compression tests of nerve conduits; where the hyperelastic–plastic constitutive law and the morphological characters of the cross sections of nerve conduits were implemented. The numerical results indicated the layered morphology of the cross sections of nerve conduits played the most important role in determining the compressive resistance. In addition, the accuracy of the numerical model was well validated by good agreement of experimental and numerical results of nerve conduit compression tests. This study helps understanding how to characterize the compressive resistance of porous polymeric nerve conduits and how the morphology influences the compressive resistance, leading to better design of fabrication setup and material selection for nerve conduits. Graphical abstract: Image 1 Highlights: The PLGA dope concentration significantly influences the morphology of nerve conduits fabricated by dry-jet wet spinning. A numerical model with the hyperelastic–plastic constitutive law and layered morphology is developed. The layered morphology plays the most important role in determining the compressive resistance of PLGA nerve conduits.